Development Of An Entrepreneurship Program To Increase The Creativity Of Students - Indra Wahyuni Firli Fangestu (Yayasan pendidikan dzurriyatul Quran, 2024)
Entrepreneurship as a driver for developed countries, generates far-reaching social benefits through achieving success in business. In the midst of this dynamic, academics and practitioners enthusiastically play a role in expanding the knowledge platform, with the aim of increasing the success rate of startups through the creativity of the younger generation. This article examines the development of entrepreneurship programs to increase student creativity. The method used is literature review, the results of writing this article are; In the era, Islamic boarding schools strive to continue to bring up entrepreneurship programs in order to equip students related to knowledge as well as practice in entrepreneurship with the aim of preparing the younger generation to face the times and preparing the entrepreneurial spirit to face challenges from the economic sector.